Natural History and Rehabilitation of the Virginia Opossum (Didelphis virginiana) - Augustine, Rose (Wildlife Rehabilitation Bulletin, 2010)
As the only pouched mammal in the United States, the Virginia opossum is a unique animal for rehabilitators. This paper focuses on the natural history and rehabilitation of orphan opossums, and addresses the common challenges faced in a captive rehabilitation setting. Some of the ideas discussed include feeding, indoor and outdoor housing, enrichment, and release considerations.